2017
DOI: 10.1111/faf.12246
|View full text |Cite
|
Sign up to set email alerts
|

The nexus of fun and nutrition: Recreational fishing is also about food

Abstract: Recreational fishing is a popular activity in aquatic ecosystems around the globe using a variety of gears including rod and line and to a lesser extent handlines, spears, bow and arrow, traps and nets. Similar to the propensity to engage in voluntary catch‐and‐release, the propensity to harvest fishes strongly varies among cultures, locations, species and fisheries. There is a misconception that because recreational fishing happens during non‐work (i.e. leisure) time, the nutritional motivation is negligible;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 164 publications
(290 reference statements)
5
119
1
Order By: Relevance
“…Responses indicated that most anglers tend to harvest some of the fish they catch but this was not true when focused specifically on catches of shortfin mako. Increasing desire to consume local food may yield changes in demand for local products including shark, and thereby participation in hunting and fishing (Cooke et al, ; Tidball, Tidball, & Curtis, ). Research is evidently needed to understand how willing consumers are to trade off sustainability and conservation when harvesting species at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Responses indicated that most anglers tend to harvest some of the fish they catch but this was not true when focused specifically on catches of shortfin mako. Increasing desire to consume local food may yield changes in demand for local products including shark, and thereby participation in hunting and fishing (Cooke et al, ; Tidball, Tidball, & Curtis, ). Research is evidently needed to understand how willing consumers are to trade off sustainability and conservation when harvesting species at risk.…”
Section: Discussionmentioning
confidence: 99%
“…These social outcomes must be maintained concurrently with biological sustainability (not unlike the commercial sector where incentives exist; Greiner et al ., ) so that the activity can continue to persist in the future. The greatest threat to biological sustainability of recreational fisheries is the exploitation of aquatic resources both directly through harvest (Cooke et al ., ) and indirectly through discard or catch‐and‐release mortality (Coggins et al ., ). However, the issues surrounding recreational fisheries are more diverse than harvest and include factors such as fisheries‐induced evolution, bait harvesting, species introductions, trophic perturbations, habitat destruction and pollution (Altieri et al ., ; Cooke & Cowx, ; Hyder et al ., ; Lewin et al ., ; McPhee et al ., ).…”
Section: Sustainability In the Context Of Recreational Fisheriesmentioning
confidence: 97%
“…Anglers are a broad, heterogeneous group that can encompass wealthy and mobile fly fishers dedicated to catch and release as well as poor and food‐insecure fishers that harvest catches (Cooke et al ., ). A diverse host of fish species is targeted by anglers visiting many different marine and freshwater habitats.…”
Section: Anglers As Agents Of Changementioning
confidence: 97%
“…Walleye Sander vitreus (Mitchill 1818) is a perciform fish native to many rivers and lakes in the Midwest of North America (Bozek et al ., ), where they are highly valued for recreation as well as for subsistence in many Canadian and US communities (Cooke et al ., ; Lester et al ., ). Sander vitreus plays a similar socio‐ecological role to that of its congener, the pike‐perch or zander Sander lucioperca (L 1758), in Europe.…”
Section: Introductionmentioning
confidence: 99%